Kontestasi Pandangan Elite Agama di Gresik tentang Nyekar di Desa Surowiti Kecamatan Panceng - Toha, Muchammad (TEOSOFI: Jurnal Tasawuf dan Pemikiran Islam, 2016)
Nyekar has become a pivotal tradition to certain groups of Javanese society as it has been believed to bring about success for every activity they do in their life. A number of public officials, for an instance, perform nyekar in order to sustain their strategic and profitable positions and to gain blessing. The article scrutinizes the opinions of religious elites in Gresik concerning nyekar in Surowiti Village, Panceng, Gresik, East Java. The study finds that there have been two existing opposing opinions held by the religious elites in relation to this tradition. The first group maintains that nyekar is allowed, while the second group argues that it is forbidden. Interestingly, each group supports their argume-nts using religious texts derived from al-Qur?ân and Hadîth. Regardless of disagreements among the religious elites vis-à-vis nyekar, the writer underlines that every religious elite should be wise in respond to such issue. It is important to educate their followers such prudent attitudes as respecting other and maintaining harmony in spite of different views they hold. It is also important to involve both theological understanding along with open, sincere, and democratic socio-historical views to create inclusive understanding of the tradition.